Corporate Performance (CP) and Satisfaction in Public Health Service Organisations (PHSO) in Eastern Province of Sri Lanka: A Use of Balanced Score Card (BSC) - Mohamed Ismail, M.B. (My University, 2014)
Eastern Province (EP) consists of three cardinal districts such as Ampara, Batticaloa and Trincomalee. Corporate performance is improved by balanced scorecard. Employeesatisfaction and patient satisfaction refer to fulfillment of their needs in public health service organisations. Public health service organizations are government hospitals. Study tries to determinefactors influencing corporate performance, employee satisfaction and patientsatisfaction in public health service organizations. Study also tries to find out the relationship between corporate performance, employee satisfaction and patientsatisfaction. Further, this study attempts to explain the impact of corporate performance on employee satisfaction and patient satisfaction. 2095 employees and 2095 patients were taken as secondary sampling units in this study from 55hospitals. For this study, data were collected from both secondary and primary sources. Data were collected using questionnaires that have higher response rate. Items of corporate performance, employee satisfaction and patient satisfaction have higher reliability. Numerous validities i.e. content, criterion and construct validity have higher validities. This study carried out factor, correlation and regression analyses. The study revealed that patient, key service line, learning & growth and resource are the factors of corporate performance. Environment, psychology and structure have been found as factors determining employee satisfaction. Core services, human element, non- human element and servicescape have been found as factors of patient satisfaction. It is concluded that corporate performance has relationships with employee satisfaction and patient satisfaction. Also, employee satisfaction has relationship with patient satisfaction. Study also concluded that around 78 percent of variations are explained by corporate performance on employee satisfaction and patient satisfaction respectively. Around 88 percent of variation is explained by employee satisfaction on patient satisfaction in public health service organizations. Findings of this study have implication for Ministry of Health and Authorities of public health service organizations to improve corporate performance, employee and patient satisfaction in public health service organisations.
Keywords: Balanced scorecard; Corporate performance; Satisfaction